Free access to hypertension and diabetes medicines among the elderly: a reality yet to be constructed Acesso gratuito a medicamentos para hipertensão e diabetes em idosos: uma realidade a ser construída - Vera Maria Vieira Paniz; Anaclaudia Gastal Fassa; Luiz Augusto Facchini; Roberto Xavier Piccini; Elaine Tomasi; Elaine Thumé; Denise Silva da Silveira; Maria Aparecida Rodrigues; Marlos Rodrigues Domingues; Andréa Dâmaso Bertoldi (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2010)
The study evaluated free access to hypertension and diabetes medicines and the reasons reported for lack of access. The sample included 4,003 elderly people living in Primary Care Unit coverage areas from 41 Southern and Northeastern Brazilian cities. Free access was higher in the Northeast (62.4%). The strategy of the Family Health Program (Programa Saúde da Família - PSF) was more effective in providing access than the traditional model, with higher results in the Northeast (61.2%) than in the South (39.6%). Around 20% of medicines included in the Hypertension and Diabetes Program and 26% of those included in the National Essential Medicines List (RENAME) were paid out of pocket. In the Northeast, 25% of insulin and 32% of oral antidiabetics were paid out of pocket. Unavailability in the public sector and a lack of money determined the lack of access. Although the PSF, Hypertension and Diabetes Program and RENAME expanded free access, supplies were insufficient. A greater connection between programs and a clear definition of responsibilities can improve medicine acquisition process, increasing the effectiveness of pharmaceutical assistance. O estudo avaliou o acesso gratuito a medicamentos para hipertensão e diabetes e os motivos para a falta de acesso. A amostra incluiu 4.003 idosos residentes na área das unidades básicas de saúde (UBS) de 41 municípios do Sul e do Nordeste brasileiro. O acesso gratuito foi maior no Nordeste (62,4%). O Programa Saúde da Família (PSF) teve mais impacto sobre o acesso que o modelo tradicional, sendo maior no Nordeste (61,2%) que no Sul (39,6%). Cerca de 20% dos medicamentos do Programa Nacional para Hipertensão Arterial e Diabetes Mellitus e 26% da Relação Nacional de Medicamentos Essenciais (RENAME) foram pagos. No Nordeste, 25% da insulina e 32% dos antidiabéticos orais foram pagos. Indisponibilidade no setor público e falta de dinheiro foram determinantes da falta de acesso. Embora o PSF, o Programa Nacional para Hipertensão e Diabetes e a RENAME ampliem o acesso gratuito, o suprimento foi insuficiente. Maior integração entre programas e clara definição de responsabilidades podem otimizar a aquisição de medicamentos, aumentando a efetividade da assistência farmacêutica.